The first love, you never forget. The last heart valve, you might remember better than the first. Issue 5 (15th April 2020) - Aranzulla, Tiziana Claudia; Musumeci, Giuseppe
Key Points: Valve‐in‐valve (VIV) transcatheter aortic valve replacement (TAVR) does not increase cerebrovascular risk compared with TAVR in native aortic valves; the only predictors of new brain lesions were age and postdilatation. Wise choice of the biological valve at the time of surgical aortic replacement, routine use of cerebral protection devices, and new therapeutic paths may be important. Larger studies are needed, hopefully with systematic postdilatation or bioprosthetic valve fracture in cases of residual high transvalvular gradients after VIV TAVR.